Earfly bite wounds in dogs in Ibadan, South-West Nigeria (2013)
A study was conducted in Ibadan, South-West Nigeria between 2005 and 2009 to determine the prevalence, risk factors and management protocols employed in earfly bite wounds in dogs. Review of case records, physical examinations and administration of structured questionnaire were used to obtain information with regard to the number of cases of earfly bite wounds presented, signalment, anatomical features, treatment modalities and response. Prevalence of earfly bite wounds was 11.73%. Sex, breed, anatomical features and management exhibited significant influence on the incidence of earfly bite wounds. Effectiveness of management protocols was low with significantly high recurrence rate. The results showed a significantly high association between earfly bite wounds and aural hematoma and otitis externa.